Maria and the plague : a Black Death survival story - Deen, Natasha; Ficorilli, Francesca (North Mankato, Minnesota : Stone Arch Books, 2021)
The people of fourteenth-century Florence, Italy, starving after years of bad weather and natural disasters, now face the Black Plague but twelve-year-old Maria is determined to survive. Includes historical note, glossary, and discussion question.
3.8
3-6
490L
V
Keywords: Black Death -- Juvenile fiction; Plague -- Juvenile fiction; Survival -- Juvenile fiction; Middle Ages -- Juvenile fiction; Families -- Italy -- Juvenile fiction; Italy -- History -- 14th century -- Juvenile fiction; Black Death -- Fiction; Plague -- Fiction; Survival -- Fiction; Middle Ages -- Fiction; Family life -- Italy -- Fiction; Italy -- History -- 14th century -- Fiction; Historical fiction